2017
DOI: 10.1080/09513590.2017.1318367
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine-hormone axis – the link between premenstrual syndrome and postpartum depression

Abstract: Premenstrual syndrome (PMS) and related disorders, and postpartum depression (PPD) can affect women to the extent that their quality of life and that of their near ones can be severely impaired. This review focuses on the different theories regarding the etiologies of PMS and PPD, and attempts to draw a link between the two. Theories focus mainly on hormonal and cytokine factors throughout different phases in the female reproductive cycle. Changes in this symptomatology during pregnancy are also reviewed, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Cytokines play an important role in innate immunity, apoptosis, angiogenesis, cell growth and differentiation. Cytokines are also involved in the process of most diseases including cancer 47,48 and reproduction disorders 23,49,50 . It has reported that proinflammatory cytokines could affect BTB permeability and enter into the seminiferous tubules to induce apoptosis of germ cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines play an important role in innate immunity, apoptosis, angiogenesis, cell growth and differentiation. Cytokines are also involved in the process of most diseases including cancer 47,48 and reproduction disorders 23,49,50 . It has reported that proinflammatory cytokines could affect BTB permeability and enter into the seminiferous tubules to induce apoptosis of germ cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…PMS is associated with substantial functional impairment comparable to that observed in dysthymia (Kues et al, 2016) and may lead to impaired work productivity (Chawla et al, 2002; Halbreich et al, 2003) and interfere with marital relationships (Frank et al, 1993), family/homemaking functions (Kuczmierczyk et al, 1992), hobbies and social activities (Heinemann et al, 2010), thereby decreasing health-related quality of life (Farrokh-Eslamlou et al, 2015). Furthermore, PMS is also an important predictor of perinatal depression (Studd and Nappi, 2012; Buttner et al, 2013; Roomruangwong et al, 2016; Stoner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, immune-mediated cytokine alterations have been found to play important roles in the underlying mechanism of PPD [4,5,6]. A possible link between PPD and the cytokine-hormone axis has also been reported [7]. However, the entire pathogenesis of PPD remains unclear.…”
Section: Introductionmentioning
confidence: 99%